2019
DOI: 10.1002/smll.201904017
|View full text |Cite|
|
Sign up to set email alerts
|

Oxidation‐Responsive Nanoassemblies for Light‐Enhanced Gene Therapy

Abstract: Microenvironment‐responsive supramolecular assemblies have attracted great interest in the biomedical field due to their potential applications in controlled drug release. In this study, oxidation‐responsive supramolecular polycationic assemblies named CPAs are prepared for nucleic acid delivery via the host–guest interaction of β‐cyclodextrin based polycations and a ferrocene‐functionalized zinc tetraaminophthalocyanine core. The reactive oxygen species (ROS) can accelerate the disassembly of CPA/pDNA complex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 40 publications
0
17
0
Order By: Relevance
“…3B). 73 The polycation part of the system, star-shaped CD-based ethanolamine-functionalized poly(glycidyl methacrylate)s, was applied to interact with p53 through an electrostatic interaction, and the zinc tetraaminophthalocyanine modified by Fc (TAPc-Fc) served as photosensitizers. In this study, 1 O 2 produced under illumination showed a limited improvement of transfection efficiency in cancer cells with high ROS levels, whereas the transfection efficiency was improved in cancer cells with low ROS levels.…”
Section: Endogenous Stimuli-responsive Supramolecular Assembliesmentioning
confidence: 99%
See 1 more Smart Citation
“…3B). 73 The polycation part of the system, star-shaped CD-based ethanolamine-functionalized poly(glycidyl methacrylate)s, was applied to interact with p53 through an electrostatic interaction, and the zinc tetraaminophthalocyanine modified by Fc (TAPc-Fc) served as photosensitizers. In this study, 1 O 2 produced under illumination showed a limited improvement of transfection efficiency in cancer cells with high ROS levels, whereas the transfection efficiency was improved in cancer cells with low ROS levels.…”
Section: Endogenous Stimuli-responsive Supramolecular Assembliesmentioning
confidence: 99%
“…58,72 As a result, redox differences between normal tissues and abnormal regions contributed to the construction of redoxresponsive assemblies (Table 2). 69,[73][74][75][76][77][78] The overexpression of both ROS (up to 100 mM) and GSH (B10 mM) in tumor cells has been repeatedly highlighted as essential triggers for controlling the intracellular drug release. 26 ROS/GSH sensitive linkers are commonly used in redox-responsive supramolecular assemblies.…”
Section: Redox-responsive Supramolecular Assembliesmentioning
confidence: 99%
“…In particular, the assembly can be decomposed upon exposure to oxidative conditions, which makes it an outstanding candidate for cancer treatment. A previous study reported that nanoparticles assembled by β-CD based polycations and Fc-functionalized zinc tetraaminophthalocyanine (TAPc-Fc) could be used for regulatory gene and photosensitivity synergistic therapy (Figure 5 a) 76 . Reactive oxygen could accelerate the decomposition of the assembly complex, which further promoted the release of p53 gene.…”
Section: Co-transport Of Regulatory Gene and Photosensitizermentioning
confidence: 99%
“… (A) Assembly process of β-CD based polycations and Fc-functionalized zinc tetraaminophthalocyanine. Adapted with permission from 76 , Copyright 2019 Wiley-VCH. (B) Schematic of multifunctional nanoparticle with imaging, drug therapy, gene therapy and hyperthermia functions.…”
Section: Figurementioning
confidence: 99%
“…In order to further extend the application of supramolecular assembly via CD-Fc interaction, we proposed a series of photosensitizer-embedded supramolecular polycationic assemblies (CPAs) with intracellular oxidation responsiveness and irradiation-controlled disassembly (Figure 6a). [48] In CPAs, one of the components, the low-cytotoxic CD-based PGEAs (CPs) were prepared to complex with p53 for gene therapy of tumor. The other components, ferrocene-modified zinc tetraaminophthalocyanine (TAPc-Fc) units, served as photosensitizers.…”
Section: Supramolecular Delivery Systems Based On Cd-ferrocene Host-gmentioning
confidence: 99%